Thoughts of Muslim Scientists Al-Kindi and Ibn Sina - Muhammad Rosul (Maklumat: Journal of Da'wah and Islamic Studies, 2023)
Al-Kindi and Ibn Sina were Muslim philosophers AL Kindi was the first Muslim philosopher to compile Islamic philosophical thought with a clear systematics. Al-Kindi's philosophical thought was a reflection of doctrines derived from classical Greek sources and Neo-Platonic heritage combined with Islamic religious beliefs. Al-Kindi opened the conversation room as an effort to integrate philosophical and religious doctrines. The knowledge of God by Al-Kindi is referred to as the early philosophy or the first philosophy; A philosophy that discourses al-Haqq as a telos that will end the entire work of philosophy. Al-Kindi divided reason according to each stage as follows; reason that is always active (is the core of all reason and all objects of knowledge), potential reason (reason that guarantees man's readiness to understand things that may be rational and require external stimulation), actual reason (potential reason that has gone out of potential limits when the soul begins to understand rational and abstract things) and reason is born (reason that has been serious about understanding rational things and turning something potential into actual). He marked the pinnacle of Islamic philosophy with his thoughts on paripatetic philosophy, known as Masya'i, which is syncretic philosophy (synthetical from the teachings of Revelation, Islam, Aristotelianism and Neoplatonism). Ibn Sina was the perfect digger and immortal translator of paripatetic philosophy who pointed to the gates of theosophical philosophy signifying the integral union of philosophy and spirituality. A century and a half after the philosophy of masya'i he led Shihabuddin Suhrawardi to the philosophy of illumination (al-ishraq).